Latin America's lithium drive: International trade perspective in the global lithium battery value chain - Moreno-Brieva, Fernando; Valdés-Valenzuela, Elicel; de Apodaca, Oihana Basilio Ruiz (Mitigation and adaptation strategies for global change, 2025)
Lithium batteries are very important for the energy transition because they allow stabilizing the energy obtained from various renewable sources, which tend to suffer large fluctuations in their energy contribution. Besides, they are widely used in a variety of high-tech products. However, the literature has scarcely addressed the importance of the analysis of the leading Latin American countries from a relative and inter-annual perspective of international trade. Hence, the purpose of this study is to analyze the international trade participation of the main Latin American economies in different components of the global lithium battery value chain, considering their share and relative evolution at the regional level, as well as their global positioning. Our findings show that Latin American countries have little presence in this value chain and that most of its main countries have a constant presence in lithium battery imports, but not in exports, although, most of these countries have experienced a positive evolution in exports and a negative evolution in imports.